Analysis of Sharia Business Strategy Implementation in the Batik Industry (Case study Batik in Pekalongan) - Hilya Diniya; Nia Amellia; Kamelia Elima’ana Mafudloh (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
The research aims to explore the marketing strategy of Pekalongan Batik Entrepreneurs with this type of research through literature and field studies that are qualitative in nature. Collection techniques using interviews, observation and documentation. The results of the study can be concluded that Pekalongan Batik Entrepreneurs have carried out a marketing mix marketing strategy. They produce a variety of batik. The methods used are payment in cash and on time, distribution to the market, opening a batik shop. The market coverage ranges from within the city, outside the city, to outside Java. They use promotions with direct sales and utilize social media technology. Batik entrepreneurs in general have applied the principles of sharia marketing mix. As for those who haven't perfected sharia principles, such as using an interest-based paylater in the payment method. In addition, there are still entrepreneurs who dispose of batik waste water directly into waterways and rivers before being processed first. The strength possessed by batik entrepreneurs in Pekalongan is that they are able to produce batik products with various types, motifs and patterns. While the weaknesses are inadequate production sites, limited capital, incompetent workforce in production, and distribution costs which are still very high for consumers who are outside the city. The opportunity for Pekalongan Batik entrepreneurs is to maximize existing technology. While the threats are raw materials which tend to rise but the selling price is getting lower and the competition of batik entrepreneurs.